Improving Prehospital Interventions: A Review of Evidence-Based Practices in Emergency Medical Services - Alsagoor, Hussain Salem; Al Haydar , Naif Abdullah; Al Haydar, Fayez Abdullah; Alasiri, Saber Mohammed; Alsagoor, Mohammed Ahmed Hussain; Gassim, Abdullah Mohammed; Alhashel, Ali Mohamed Ali; Almasad , Saleh Mana Mohammad; Al jumhur, Mohammed Ali Mutlaq; Alhaydar, Ibrahim Mana (Journal of Ecohumanism, 2024)
Emergency Medical Services (EMS) play a critical role in providing urgent care and stabilizing patients before they reach the hospital. The effectiveness of EMS interventions can significantly influence patient outcomes, making evidence-based practices essential in prehospital care. This review explores the latest evidence-based prehospital interventions in airway management, hemorrhage control, cardiac arrest response, pharmacological support, and trauma stabilization. By evaluating the current literature, this article highlights the impact of specific interventions on patient survival rates, recovery quality, and overall morbidity. Additionally, it examines challenges faced by EMS providers, including training limitations, resource disparities, and protocol adherence issues. Best practices such as standardized protocols, technology integration, and continuous training programs are discussed to address these challenges and improve EMS care. The findings underscore the importance of adopting and adhering to evidence-based practices in EMS to enhance patient outcomes and provide a foundation for future research on advanced prehospital interventions.